Risk factors of stunting incidence among children aged 6-23 months in fishing families in Brebes Regency - Hanin Maulida Fasya; Dodik Briawan; Ali Khomsan (Journal of Health and Nutrition Research, 2026)
Stunting remains a major public health problem, particularly in coastal communities where poverty and limited dietary diversity are prevalent. Children in fishing families are vulnerable due to low household income, inadequate food intake, and exposure to infections. This study aimed to identify and analyze the risk factors associated with stunting among children aged 6–23 months in fishing families in Brebes Regency, Central Java. A matched case-control study was conducted from April to May 2025 in three coastal villages (Kluwut, Grinting, and Pulogading), Bulakamba Subdistrict, Brebes. A total of 132 subjects were enrolled, consisting of 44 stunting cases and 88 controls matched by age. Data were collected on child, maternal, and household characteristics, dietary intake, and health status. Statistical analyses included Chi-square test and Binary Logistic Regression to determine significant risk factors (p<0.05). The results showed that children with a history of pulmonary TB had an 9.622 times higher risk of being stunted (OR = 8.120; 95% CI: 1.009–91.735; p = 0.049). Inadequate energy intake (≤89% RDA) had an 8.12 times higher risk of stunting (OR = 8.120; 95% CI: 2.552–25.839; p = 0.001). Birth length <48 cm increased the risk of stunting by 4.105 times ((OR = 4.105; 95% CI: 1.593-10.575; p = 0.003). Meanwhile, age 6-11 months showed a protective effect (OR=0.343; 95% CI: 0.135-0.869; p=0.024).